The Need of Chest Computer Tomography in The Assessment of Mediastinal Seminoma and Non Seminomatous Germ Cell Tumors - Icksan, Aziza; Luhur, Reny; -, Elisna; -, Heriawati (Indonesian Journal of Cancer, 2007)
Germ cell tumor mediastinum merupakan salah satu dari masa mediastinum anterior yang terdiri dari teratoma, seminoma dan non seminomatous. Diferential diagnosa dari germ cell tumor pada mediastinum anterior meliputi massa thymus, massa tiroid dan lymphoma. Dalam membuat diagnosa, disamping gejala klinis dan usia pasien, pemeriksaan seromarker serta temuan foto toraks dan CT toraks sangat membantu. Diagnosa pasti ditegakkan berdasarkan pemeriksaan sitologi dan histopatologi dari spesimen yang berperan penting sebagai baku emas.Penentuan lokasi tumor yang tepat sangatlah penting dalam penanganan pasien. Foto toraks merupakan pemeriksaan imaging awal yang dilakukan pada pasien yang sudah diketahui atau dicurigai menderita germ cell tumor mediastinum. Pemeriksaan Chest CT dengan kontras merupakan prosedur rutin dalam penanganan germ cell tumor mediastinum.Kasus non seminomatous dan seminoma germ cell tumor pada mediastinum anterior dilaporkan pada laki laki berusia 17 dan 15 tahun. Pada kedua pasien ini telah dilakukan pemeriksaan foto toraks dan CT toraks dengan menggunakan kontras media.Kata kunci : germ cell tumor mediastinum, seminoma, non seminomatous, foto toraks, CT toraks. ABSTRACTVÂ»**Mediastinal germ cell tumor is one of the anterior mediastinal mass which consists of teratoma, seminoma and non seminomatous. The differential diagnosis of the anterior mediastinal germ cell tumor such as thymic mass, thyroid mass and lymphoma. The diagnosis depends on some criteria such as, clinical finding, the age of the patient, sero markers, location of the mass and findings on the chest radiograph and chest CT. Cytology and histopathology finding from the specimens are paramount important as a gold standard.Accurate assessment of the location is very important to manage the patient. Chest radiograph is usually the first imaging study obtained in a patient with known or suspected of mediastinal germ cell tumor, and for further evaluation enhanced Chest CT nowadays has become the routine procedure in assessing mediastinal germ cell tumor.Cases of the mediastinal non seminomatous and seminoma germ cell tumors were reported in a 17 and 15 year old males. Chest radiograph and enhanced chest CT were used to diagnosing and assessing of the patients.Key word : mediastinal germ cell tumor, seminoma, non seminomatous, chest radiograph , Enhanced chest CT.